Soundtrapped? Socio-material perspectives on collaborative teaching within the music classroom - Holdhus, Kari; Christophersen, Catharina; Partti, Heidi (SAGE, 2022)
This article draws on a classroom project to explore the complexities of collaborative teaching within the music classroom, where a professional team collaborated to facilitate digital music-making at a lower secondary school in Norway during a student teacher practicum placement. The collaborative team, including in-service and pre-service teachers, researchers, and a professional musician, facilitated a composing project by means of the digital audio workstation (DAW) Soundtrap. The purpose was to shed light on the complexity and emergence of the collaborative music project; how material, structural, and educational conditions impacted the process; and the pre-service music teachers’ ways of handling a complex situation. The study was theoretically guided by a socio-material perspective, more specifically by complexity theory, and an abductive analysis was performed. In keeping with the nonlinearity and complex causality of socio-materialism and complexity theory, the researchers created three reflexive viewpoints: emergence, enabling constraints, and entanglements. The results show that technological and technical issues permeated the classroom work, making it difficult to separate social and material aspects of the project. Awareness of the entanglement of social, institutional, historical, and material dimensions of education thus can provide a useful framework for emerging music teachers’ professional development. In this way, our findings support the claim that music teacher education should aim at helping pre-service teachers prepare for encounters with complex and versatile educational situations.
Keywords: musiikkikasvatus; musiikki; opettajankoulutus; yhteistyö; opetus; luokkatyöskentely; opettajat; yhteistoiminnallinen oppiminen